(untitled) (Politeja, 2025)
The period between the World Wars is a relatively uncharted area in the study of South African security policy, often overlooked in the wider discussion of the nation’s political and defence strategies. While recent scholarly work has attempted to shed light on this complex area, limitations in primary sources and a lack of a holistic approach have hindered a full understanding of the diverse political forces at play in the Union of South Africa at this time. This study seeks to fill these gaps by scrutinising South Africa’s security policies across these two decades. Utilising a rich array of archival resources, the research meticulously outlines South Africa’s rearmament strategy in the 1930s. It explores the driving factors behind this strategy and its impact on the international arena, especially in terms of diplomatic relations between Pretoria and London and South Africa’s geopolitical position in Africa. Additionally, this research examines South Africa’s ambivalent stance towards involvement in another major conflict, linking this reluctance to the rising tide of Afrikaner nationalism which significantly shaped the nation’s socio-political framework. Overall, this study offers a thorough historical-political analysis to understand how internal and external political forces shaped South Africa’s security policies in the years between the World Wars.